Risk factors, treatment, and outcome in dogs and cats with subdural hematoma and hemispheric collapse after ventriculoperitoneal shunting of congenital internal hydrocephalus - Farke, Daniela; Siwicka, Anna K.; Olszewska, Agnieszka; Czerwik, Adriana; Büttner, Kathrin; Schmidt, Martin J.; Justus Liebig University Giessen (My University, 2023)
Background: Overshunting and hemispheric collapse are well-known complications after ventriculoperitoneal shunt (VPS) implantation. Risk factors that predispose to overshunting, treatment options, and prognosis after therapeutic intervention have not been described. Hypothesis/Objectives: To identify preoperative risk factors for overshunting, the effect of surgical decompression, and their outcomes. Animals: Seventy-five dogs and 7 cats. Methods: Retrospective case cohort study. Age, breed, sex, body weight, number of dilated ventricles, ventricle brain ratio, intraventricular pressure, and implanted pressure valve systems were evaluated as possible risk factors. Results: Overshunting had a prevalence of 18% (Cl 95% 9.9-26.66). An increase of 0.05 in VBR increased the risk of overshunting by OR 2.23 (Cl 95% 1.4-3.5; P = .001). Biventricular hydrocephalus had the highest risk for overshunting compared to a tri- (OR 2.48 with Cl 95% 0.5-11.1) or tetraventricular hydrocephalus (OR 11.6 with Cl 95% 1.7-81.1; P = .05). There was no influence regarding the use of gravitational vs differential pressure valves (P > .78). Overshunting resulted in hemispheric collapse, subdural hemorrhage, and peracute deterioration of neurological status in 15 animals. Subdural hematoma was removed in 8 dogs and 2 cats with prompt postoperative improvement of clinical signs. Conclusions and Clinical Importance: Biventricular hydrocephalus and increased VBR indicate a higher risk for overshunting. The use of differential valves with gravitational units has no influence on occurrence of overshunting related complications and outcomes. Decompressive surgery provides a favorable treatment option for hemispheric collapse and has a good outcome.
Keywords: ddc:630